Performance and emission characterization of a common-rail compression-ignition engine fuelled with ternary mixtures of rapeseed oil, pyrolytic oil and diesel - Mikulski, Maciej; Ambrosewicz-Walacik, Marta; Duda, Kamil; Hunicz, Jacek (Elsevier, 2019)
Biofuels are one of the short-term alternatives for reducing the well-to-wheel greenhouse gas footprint of transport. In the framework of compression-ignition engine fuels. This study investigates the feasibility of using cold-pressed rapeseed oil as a biocomponent, admixed with distilled tyre pyrolytic oil, as an energy-efficient alternative to commonly considered methyl ester-based mixtures in diesel fuel. Selected ternary and binary fuel blends are subjected to engine tests. Their scope covers 80% of the engine map and aims at identifying tradeoffs between fuel composition, engine performance and emissions. The results show that fuel mixtures containing a large fraction of rapeseed oil (up to 55% by volume) can be effectively combusted when pyrolytic oil distillate is introduced as the additive. The deterioration in brake efficiency for such fuel does not exceed 1.2% with respect to diesel baseline. At the same time, the results are superior in terms of both efficiency and emissions when compared to FAME-based biodiesel. Finally, with indicated efficiencies on a similar level as the diesel baseline, suggesting improved burning rate with pyrolytic oil addition, the study identifies parasitic losses in fuel injection equipment as a significant contributor to the overall efficiency penalty for the examined ternary mixtures.
Keywords: diesel engine; rapeseed oil; pyrolytic oil; waste tyres; efficiency analysis; exhaust emissions; fi=Energiatekniikka|en=Energy Technology|